2007
DOI: 10.2319/070606-280.1
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Conditioner for Resin-Modified Glass Ionomers in Bonding Orthodontic Brackets

Abstract: Objective: To evaluate a new self-etch conditioner used with resin-modified glass ionomers (RMGIs) in bonding orthodontic brackets. Materials and Methods: Sixty human molars were cleaned, mounted, and randomly divided into three groups. In group 1 (control), 20 orthodontic brackets were bonded to teeth using Transbond Plus Self-etching Primer; in group 2, 20 brackets were bonded using an RMGI with a 10% polyacrylic acid conditioner. In group 3, 20 brackets were bonded using Fuji Ortho LC with a new norinse sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…This modification has improved the performance of this cement as an orthodontic bonding agent via the addition of resinous components. However, even this higher BS remains below the strengths that were recorded for composite resins [8][9][10] . The use of 5.25% sodium hypochlorite (NaOCl) as a enamel deproteinizing agent prior to acid conditioning and bracket bonding with RMGIC has been suggested as a means of increasing bond strength.…”
Section: Introductionmentioning
confidence: 69%
“…This modification has improved the performance of this cement as an orthodontic bonding agent via the addition of resinous components. However, even this higher BS remains below the strengths that were recorded for composite resins [8][9][10] . The use of 5.25% sodium hypochlorite (NaOCl) as a enamel deproteinizing agent prior to acid conditioning and bracket bonding with RMGIC has been suggested as a means of increasing bond strength.…”
Section: Introductionmentioning
confidence: 69%
“…This is explained by the fact that the polyacrylic acid etching agent used in these groups has an etching pattern with less extension and depth than that of phosphoric acid, as observed in several other studies. [7][8][9][10][11][12][13][14] In a study conducted by Smith and Cartz, 15 etching with polyacrylic acid caused little demineralization of the enamel surface. Bishara and Ostby 8 also observed that teeth etched with polyacrylic acid had a significantly lower shear bond strength than teeth etched with 37% phosphoric acid before being bonded with RMGIC, which was proved in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…With the intention of combining important characteristics of the two materials, such as shear bond strength and fluoride release, RMGICs were developed, which release fluoride without compromising the bond strength to the tooth surface. [10][11][12] The bond strength between orthodontic accessories and enamel may be compromised by the presence of the acquired pellicle, which covers the soft and hard tissues in the oral region, particularly the surface of tooth enamel. This membrane is a biofilm free of bacterial colonization, and its most abundant components are proteins, glycoproteins, enzymes, and mucins or their derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros datos son similares a los reportados por Nascimento et al (19) y Pithon et al (29); esto puede explicar la idea de que los efectos de los agentes químicos pueden causar las fallar de adhesión en la interfase esmalte adhesivo. Según Bishara et al, el hecho de que la falla ocurra en la interfase bracket/adhesivo se convierte en un fenómeno de protección para el esmalte dental, ya que la estructura del esmalte permanece intacta, previniendo posibles daños durante el proceso de remoción de los brackets (30).…”
Section: Discussionunclassified